Managing facilitator competencies in learning circles - Wee, Sheila Esther Suyin. (2008)
The purpose of this study was to distill the critical Learning Circle management factors which lead to effective action research amongst teachers. The study entailed a detailed look at what skills and attributes the Learning Circle facilitator needs to bring to the research situation to help teacher-researchers engage and persist in the inquiry into their practice.